HUBUNGAN LAMA PEMAKAIAN DEPO MEDROKSIPROGESTERON ASETAT DENGAN GANGGUAN MENSTRUASI DI PERUMAHAN PETRAGRIYA INDAH PURWODADI TAHUN 2008 - Setyaningrum, Agustina Catur; Sehmawati, Sehmawati (Jurnal Berita Ilmu Keperawatan, 2008)
The use of Depo Medroksiprogesteron Asetat ( DMPA ) can give side effects to the change of menstrual pattern. The changes can be in the form of menstrual changing cycle, prolonged menstrual period, and spotting. Those menstrual pattern effect depends on how long we use DMPA. General objective of this research is to find out the relationship of the prolonged- use of DMPA towards menstrual disturbances happened in Petragriya Indah Estate Purwodadi. While the specific objective of this research is to find out the relationship of prolonged – use of DMPA towards menstrual cycle, prolonged menstrual period and spotting. Research design used is An Analytical survey based on cross sectional approach. Research population used is all acceptors of DMPA registered in Petragriya Indah Estate Purwodadi in December 2007 ( totally 63 acceptors ). Sampling technique used is simple random sampling involving 54 respondent. Interview is used as the method of data collection, while Spearmean correlation test supported by SPSS computer version 11,5 is used as the method of Data Analysis. The result of univariat analysis seems to show that menstrual period history before using DMPA is mostly regular and natural. In the early injection ( first trimester or 3 month of 1 ), 54 DMPA acceptors have experienced prolonged- cycle of olygomenorrea totally 4 people, and more than 3 months afterward 3 people experienced amenorrea while 20 of them don’t experience menstruation at all. The result of bivariat analysis seems to show that prolonged use of DMPA relates to menstrual cycle as it is shown by Spearman correlation test result, p value = 0,012, r = 0,341. It also relates to menstrual duration as shown by its statistical test result, p value = 0,010, r = - 0,346. Finally, it also relates to spotting as illustrated by its statistical test result, p value = 0,004, r = -0,382.